Eco-sensitivity and its spatial distribution in Hangzhou - TAO Xing-ming; ZHANG Jian-xing; WANG Yu-feng; WANG Fei-er (浙江大学学报. 农业与生命科学版, 2006)
Eco-sensitivity evaluation is a base for ecological regionalization. The ecological factors including sensitivities to soil erosion, to bio-diversity protection and to acid rain in Hangzhou were analyzed by using global information system (GIS) technology and the model of multifactor summation with different weight in this paper. The results show that the difference of spatial distribution between these factors was significant, and the spatial area of Hangzhou ecosystem can be divided into sub-region of weak, medium, and high sensitivity, with the individual areas of these sub-regions amounting to 10.91%, 59.63% and 29.4% of the total area respectively. In light of the assessment result of eco-sensitivity, the actions of environmental protection and the design of industry development are suggested for supporting to national distribution of industrial and regional environment protection.